Epilepsy, antiepileptic drugs, and the risk of major cardiovascular events. (27th May 2021) - Lee‐Lane, Elinor; Torabi, Fatemeh; Lacey, Arron; Fonferko‐Shadrach, Beata; Harris, Daniel; Akbari, Ashley; Lyons, Ronan A.; Rees, Mark I.; Sawhney, Inder; Halcox, Julian; Powell, Rob; Pickrell, William Owen
Summary: Objective: This study was undertaken to determine whether epilepsy and antiepileptic drugs (including enzyme‐inducing and non‐enzyme‐inducing drugs) are associated with major cardiovascular events using population‐level, routinely collected data. Methods: Using anonymized, routinely collected, health care data in Wales, UK, we performed a retrospective matched cohort study (2003–2017) of adults with epilepsy prescribed an antiepileptic drug. Controls were matched with replacement on age, gender, deprivation quintile, and year of entry into the study. Participants were followed to the end of the study for the occurrence of a major cardiovascular event, and survival models were constructed to compare the time to a major cardiovascular event (cardiac arrest, myocardial infarction, stroke, ischemic heart disease, clinically significant arrhythmia, thromboembolism, onset of heart failure, or a cardiovascular death) for individuals in the case group versus the control group. Results: There were 10 241 cases (mean age = 49.6 years, 52.2% male, mean follow‐up = 6.1 years) matched to 35 145 controls. A total of 3180 (31.1%) cases received enzyme‐inducing antiepileptic drugs, and 7061 (68.9%) received non‐enzyme‐inducing antiepileptic drugs. Cases had an increased risk of experiencing a major cardiovascular event compared to controls (adjusted hazard ratio = 1.58, 95% confidence interval [CI] = 1.51–1.63, p  < .001). There was no notable difference in major cardiovascular events between those treated with enzyme‐inducing antiepileptic drugs and those treated with non‐enzyme‐inducing antiepileptic drugs (adjusted hazard ratio = .95, 95% CI = .86–1.05, p = .300). Significance: Individuals with epilepsy prescribed antiepileptic drugs are at an increased risk of major cardiovascular events compared with population controls. Being prescribed an enzyme‐inducing antiepileptic drug is not associated with a greater risk of a major cardiovascular event compared to treatment with other antiepileptic drugs. Our data emphasize the importance of cardiovascular risk management in the clinical care of people with epilepsy.